The Key To Islamic School Teacher Happiness: Organizational Climate And Positive Thinking - Erika Dian Intara; Tri Nai’mah; Imam Faisal Hamzah; Herdian (Mudir : Jurnal Manajemen Pendidikan, 2024)
Human resource development (HRD) in education is crucial, particularly for teachers, making it essential to enhance workplace happiness. This study aims to investigate the impact of organizational climate and positive thinking on teachers' happiness at work in Islamic Vocational School “X” in Banyumas, Central Java. The sample consisted of 107 teachers from SMK Islam “X” in Banyumas, Central Java, selected through simple random sampling. Data collection instruments included organizational climate scale, positive thinking scale, and happiness at work scale. Data analysis involved multiple linear regression techniques. The results indicate a significant influence of organizational climate on happiness at work (t = 9.121; p = 0.54 < 0.05) and a significant impact of positive thinking on happiness at work (t = 9.231; p = 0.159 < 0.05). Simultaneous analysis revealed an F score of 60.258; sig. (p) = 0.000 < 0.05, indicating that organizational climate and positive thinking play a crucial role in determining teachers' happiness at work.